Effectiveness of a multicomponent exercise intervention in community-dwelling older Chinese people with cognitive frailty: protocol for a mixed-methods research - Ning, Hongting; Chen, Fenghui; Li, Junxin; Du, Yan; Chen, Xi; Wu, Shuang; Joseph, Abigael; Gao, Yinyan; Cao, Zeng; Feng, Hui (Frontiers in Aging Neuroscience, 2024)
Aims To evaluate the effectiveness of a multicomponent exercise intervention and to clarify the underlying mechanisms of the program in community-dwelling older adults with cognitive frailty. Additionally, the perception of participants in the program will be explored. Design A mixed-methods design, including a randomized controlled trial and an exploratory qualitative study, was used. Methods Each group consists of 41 participants. The experimental group will undergo a 12-week multicomponent exercise intervention, including warm-up, exergaming aerobic exercise, elastic-band resistance exercise, and cool-down. This intervention was developed based on the Health Belief Model (HBM) and Self-Efficacy Model (SEM). The control group will not receive any intervention. Physical frailty and cognitive function will be considered as primary outcomes. Data will be collected both at baseline and at the end of the intervention period. Fisher’s exact test, analysis of covariance, and generalized linear models will be conducted to compare mean changes between the two groups. Additionally, the mediation models will be used to examine whether any intervention effects are mediated through exercise self-efficacy. Discussion The findings of this study are anticipated to provide valuable insights for healthcare providers, enabling them to learn about effective strategies to enhance exercise adherence and promote improved functionality, independence, and quality of life for older adults with cognitive frailty. Clinical trial registration: [https://clinicaltrials.gov/], identifier [ChiCTR2200058850].